PROJECT BASED-LEARNING IMPLEMENTATION IN DEVELOPING STUDENTS' CRITICAL THINKING SKILLS - Nabilah Fairuz ryadi, - (2018)
Project-based learning (PBL) is believed to build students' critical thinking skills. This study aims to explore the ways PBL develop students' critical thinking skills in EFL classroom. The design employed in this research was a qualitative case study with one class of tenth grade students as the participants. The data obtained through observation, interview, and collection of students' work.The findings revealed that there are five processes of PBL that developed students' critical thinking skills: (1) building background knowledge, (2) working with group to plan and construct video story scenario, (3) recording scenes, (4) editing the video, and (5) evaluating the video product and the whole process of the project. Through these 5 PBL processes, critical thinking developed includes: interpretation, analysis, evaluation, inference, explanation, and self-regulation. In general, critical thinking levels of students were at the acceptable levels, which frequently interpreted, identified arguments, offered analyses and evaluations of alternative points of view, drewwarranted conclusion, justified procedures, and opened to new idea. This study also discovered that the most challenging process in developing students' critical thinking skills is the process of working with group to plan and construct a video story scenario. In addition, the used of ICT in PBL supported the development of students' critical thinking skills. Moreover, evaluation process played a role as a tool for reflection that further encouraged students' critical